Inside Front Cover: Evaluation of the Aortopathy in the Ascending Aorta: The Novelty of Using Matrix‐Assisted Laser Desorption/Ionization Imaging. Issue 1 (18th January 2021) - Mohamed, Salah A.; Taube, Eliane T.; Thiele, Herbert; Noack, Frank; Nebrich, Grit; Mohamady, Kamal; Hanke, Thorsten; Klein, Oliver
Abstract : The image illustrates the potential of MALDI Imaging to explore differences in spatial proteomic alterations in aneurysmal ascending aortic tissues from patients with aortic valve vitium (BAV), normal aortic valve (TAV), and aneurysmal tissue of connective tissue disorder (MFS). MALDI Imaging in combination with histopathological assessment are feasible to explore pathogenesis of the ascending thoracic aortic aneurysms. This is reported by Salah A. Mohamed, Eliane T. Taube, Herbert Thiele, Frank Noack, Grit Nebrich, Kamal Mohamady, Thorsten Hanke, and Oliver Klein in article 2000047 .